2006
DOI: 10.1038/sj.emboj.7601215
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor gene identification using retroviral insertional mutagenesis in Blm-deficient mice

Abstract: Retroviral insertional mutagenesis preferentially identifies oncogenes rather than tumor suppressor (TS) genes, presumably because a single retroviral-induced mutation is sufficient to activate an oncogene and initiate a tumor, whereas two mutations are needed to inactivate a TS gene. Here we show that TS genes can be identified by insertional mutagenesis when the screens are performed in Blm-deficient backgrounds. Blm-deficient mice, like Bloom syndrome patients, have increased frequencies of mitotic recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
126
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(128 citation statements)
references
References 40 publications
1
126
1
Order By: Relevance
“…A genome-wide screen of 44 MoMuLVinduced T cell lymphomas for novel targets of proviral DNA integration yielded clones of 149 independent provirus integrations. Six of these integrations, cloned from five independent tumors, had targeted a gene we named Ndy1, also known as FBXL10 or JHDM1B (9,10,16,17). Two of them were cloned from a single tumor, D0, suggesting that this tumor consists of at least two populations of cells, both of which carry an inte-grated provirus in this locus.…”
Section: Ndy1 Is a Common Target Of Provirus Integration In Momulv-inmentioning
confidence: 99%
See 2 more Smart Citations
“…A genome-wide screen of 44 MoMuLVinduced T cell lymphomas for novel targets of proviral DNA integration yielded clones of 149 independent provirus integrations. Six of these integrations, cloned from five independent tumors, had targeted a gene we named Ndy1, also known as FBXL10 or JHDM1B (9,10,16,17). Two of them were cloned from a single tumor, D0, suggesting that this tumor consists of at least two populations of cells, both of which carry an inte-grated provirus in this locus.…”
Section: Ndy1 Is a Common Target Of Provirus Integration In Momulv-inmentioning
confidence: 99%
“…Ndy1 encodes a protein that contains a JmjC domain (9,10,16,17), a CXXC zinc finger, a PHD zinc finger, a proline-rich region (PRR), an F-box, and a leucine-rich repeat (LRR) (Fig. 1 A and ref.…”
Section: Ndy1 Is a Common Target Of Provirus Integration In Momulv-inmentioning
confidence: 99%
See 1 more Smart Citation
“…JMJD5 was initially identified as a putative tumor suppressor that regulates genome integrity in Blm-deficient mice, 46 and JMJD5 overexpression inhibits cell growth and tumorigenicity in hepatocellular carcinoma cells. 32 However, in lung, colon and breast cancers, JMJD5 functions as a putative oncogene that promotes cancer cell proliferation, invasion and cellular metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…56 These functional observations and the fact that its relatives Chd2, Chd3, and Chd9 have been identified as CISs in MoMuLV-based RIM screens suggest that Chd4 is indeed a likely oncogene. 48,57 Rag2 encodes the recombination activating gene 2 (Rag2), which in concert with Rag1 is directly involved in V(D)J recombination in lymphoid cells. Rag2 expression is normally strictly confined to lymphoid cells, and it has been suggested that inappropriate induction of the Rag complex could induce genomic instability due to unauthorized recombination.…”
Section: Identification and Analysis Of Srs19-6-induced Retroviral Tagsmentioning
confidence: 99%